A Systematic Review of Continuance Intention to Use Mobile Health (2020–2024) - Subrata; Lisana (Green Publisher Indonesia, 2026)
The rapid advancement of digital technologies in healthcare has led to the widespread adoption of mobile health (mHealth) applications, offering users convenient access to health services. However, despite increasing downloads, many users discontinue usage after initial adoption, highlighting the issue of low continuance intention. This paper aims to systematically review the empirical literature to identify the key factors influencing users’ continued use of mHealth applications. A systematic literature review (SLR) was conducted using the PRISMA 2020 protocol and structured with the PICO framework. A total of 20 peer-reviewed studies published between 2020 and 2024 were analyzed. The review identified that perceived usefulness, satisfaction, ease of use, and trust are the most frequently studied and influential factors. Several theoretical models, such as the Technology Acceptance Model (TAM), Expectation-Confirmation Model (ECM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Self-Determination Theory (SDT), were also widely applied. Additionally, the findings suggest that contextual elements like age, digital literacy, and chronic health conditions significantly affect continuance intention, especially among the elderly and specific user groups. The results of this study provide a comprehensive understanding of the multidimensional determinants of sustained mHealth usage and offer valuable insights for application developers, healthcare providers, and researchers to design more user-centered and effective digital health solutions.